A questão da interpretação na teoria do direito: uma análise do interpretativismo de Ronald Dworkin na perspectiva de Andrei Marmor - Norões, Victor Gerson Batista de (2020)
The purpose of this dissertation is to discuss different accounts of interpretation in the context of the Hart-Dworkin debate, and more specifically, Andrei Marmor's analysis of Ronald Dworkin's objections to legal positivism in Law’s Empire, in which in advances the notion that every conclusion about the content of the law is a result of interpretation; and that the very nature of an interpretation is such that it necessarily involves evaluative considerations. Thus, the main objective will be to assess Marmor’s response to Dworkin’s criticisms. As one of Dworkin's most important contributions the debate, Law’s empire inaugurated a new conception of jurisprudence, interpretivism, seen as an alternative to legal positivism and jusnaturalism. Thereafter, this author challenged the notion that the existence and content of law would be determined by social conventions, in addition to questioning the methodology of analytical jurisprudence, which dealt with a morally neutral description of its object. After all, was Dworkin correct about these theoretical claims? Offering a counterpoint to these arguments, Marmor sought to defend both methodological and substantial aspects of legal positivism, arguing that the constructive interpretation model provided by Dworkin was grounded in misguided premises. Inserting itself in the debate between these two authors, this work is divided into three chapters, which seek to explore: i) Dworkin's criticisms to legal positivism, and how his different arguments relate to each other; ii) the objections in Law’s Empire, amid the responses of other exponents of exclusive positivism, among them Joseph Raz, Kevin Toh and Scott J. Shapiro; iii) and, finally, Marmor's reply to Dworkin, focusing on the main aspects of his response and the pertinence of his analysis. As conclusion, it is proposed that Marmor's response was effective in demonstrating the philosophical relevance of legal positivism and in refuting some of Dworkin's arguments in Law’s Empire, above all by shedding light on the concept of interpretation, supported by reflections on the method of analytical jurisprudence and on the role of language in law. Nevertheless, if Dworkin's criticisms are to be considered in context, the defense of conventionalism in Interpretation and Legal Theory does not answer how a rule of recognition in the form of social conventions can (or cannot) accommodate normative disagreements regarding the ultimate criteria of legal validity.